2018
DOI: 10.2139/ssrn.3292740
|View full text |Cite
|
Sign up to set email alerts
|

Lending Corruption and Bank Loan Contracting: Cross-Country Evidence

Abstract: Lending corruption is an important agency problem for banks. Using data from the World Bank Business Environmental Survey, we find that in countries with more corruption, banks give more favorable loan terms to borrowers. This relation is stronger when firms are under more financing constraints, consistent with corruption being important to obtaining favorable loan terms when the supply of debt capital is tighter. In line with the expectation that monitoring constrains agency problems, this relation is weaker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 65 publications
(132 reference statements)
0
3
0
Order By: Relevance
“…This result is consistent with Jiang et al (2018) in which lower corruption is found to moderate loan growth and higher corruption makes loan terms more favorable to lenders. 11 Table 4 on the other hand, summarizes the results of applying equation (2).…”
Section: Loan Growth Corruption and Bank Performance: Baseline Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This result is consistent with Jiang et al (2018) in which lower corruption is found to moderate loan growth and higher corruption makes loan terms more favorable to lenders. 11 Table 4 on the other hand, summarizes the results of applying equation (2).…”
Section: Loan Growth Corruption and Bank Performance: Baseline Resultssupporting
confidence: 89%
“…On balance, however, there is stronger evidence in the literature on the "sand in the wheels" compared to the "grease the wheels" viewpoint. Jiang et al (2018) propose a "protection against risk" hypothesis to explain the effect of corruption on loan growth. Under this hypothesis banks in countries where bribing bank officials is common, lending policies will be tightened because lenders have greater pre-contracting expectations that corruption at the bank official level will increase costs.…”
Section: Corruption and Performancementioning
confidence: 99%
“…The disposition of the banks, in aiding and abetting corrupt government officials to steal public funds and providing a haven for them to hide their illicit fund or legalise the proceed of corruption because of their drive for profit is the motivation for this study. Previous studies have examined bank lending corruption and various dimension and consequences (Barth et al , 2016; Barry et al , 2016; and Jiang et al , 2018). The uniqueness of this study from previous studies on corruption in the banking sector is that it fills the gap in the literature on the other side (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the stronger regulatory environment was effective in the case of family-owned bank-induced corruption but not sufficient for state-owned bank-induced corruption. Jiang et al (2018) examined the influence of lending corruption on bank loan contracting using World Bank business environment survey. They found that the bank gave favourable loan term to borrowers with higher financial constraints in countries with more lending corruption.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation